Control schemes for district heating substations considering user-defined building's indoor temperature. (15th March 2021) - Sleptsov, Arseniy; Crisostomi, Emanuele; Bischi, Aldo
Abstract: Buildings' space heating (SH) systems are connected to the district heating (DH) systems via heat exchangers (HEs) located at substations. In the HEs, proportional–integral (PI) controllers adjust the DH mass flow rate by monitoring the SH system's supply temperature according to the set-points given by an outdoor temperature compensation curve without any feedback about a building's indoor temperature. We introduce two alternative controller schemes with improved configurations concerning energy savings and power peak shaving. The first scheme is a PI controller monitoring the indoor temperature according to its set-points by changing the source-side mass flow rate in the HE. The second one is a cascaded PI controller consisting of the inner and outer loops of PI logic. The inner loop monitors the SH system's supply temperature according to the set-points altered by the outer loop monitoring the indoor temperature based on its set-points. The simulation studies in the TRNSYS software environment show that the new controllers' configurations with the tuned PI constants enable the flexible maintenance of indoor temperature, boosting buildings' integration into modern DH systems' operation. By tuning the PI controllers' parameters, one can manage the trade-offs between indoor temperature maintenance, energy use, and thermal load peaks. Moreover, the cascaded PI controller may reduce thermal load peaks occurring during set-point changes by 26%. On top of that, such a controller's scheme can be developed to retrofit conventional controller's one, simplifying its implementation and accelerating the transition from the traditional generation of DH systems into the new one. Highlights: A TRNSYS building model was developed and verified. The model consists of a space heating system and substation heat exchanger. Comparison of proposed controllers was conducted. The new controllers may maintain flexible indoor temperature set-points. Thermal load peaks may be reduced by 26%.